Recognizability in Stochastic Monoids - A. Kalampakas; O. Louscou-Bozapalidou; S. Spartalis (Ratio Mathematica, 2014)
Stochastic monoids and stochastic congruences are introduced and the syntactic stochastic monoid M L associated to a subset L of a stochastic monoid M is constructed. It is shown that M L is minimal among all stochastic epimorphisms h : M → M ′ whose kernel saturates L. The subset L is said to be stochastically recognizable whenever M L is finite. The so obtained class is closed under boolean operations and inverse morphisms.